Idiopathic nodular glomerulosclerosis: a case report - Landry, Claudia; Rodriguez-Calero, Antonio; Vogt, Bruno; Bocchi, Federica (Frontiers in Medicine, 2024)
Idiopathic nodular glomerulosclerosis (ING) is a rare condition characterized by poor renal prognosis. The pathophysiology remains incompletely understood. Histologically, it closely resembles diabetic nephropathy. The development of this disease seems to be influenced by factors such as metabolic syndrome, particularly hypertension and glucose intolerance, along with active smoking. We report a case of ING in an obese 71-year-old male patient who had a long history of untreated hypertension and smoking. The patient underwent conservative treatment involving the administration of an angiotensin-2 receptor antagonist and dapagliflozin, resulting in favorable disease progression. Additional therapeutic measures, such as discontinuation of smoking and efforts towards weight loss, are strongly advised. Furthermore, regular screening for diabetes in the follow-up is crucial, as it can play a pathophysiological role in the disease and may manifest at a later stage, as observed in our clinical case.